P373 Psoriasis and psoriasiform skin lesions in patients with Inflammatory Bowel Disease treated with infliximab: a pharmacokinetic analysis. (27th May 2021) - Rodrigues, I; Damião, F; Serrazina, J; Fernandes, S; Bernardo, S; Gonçalves, A R; Moura Santos, P; Baldaia, C; Valente, A; Correia, L; Tato Marinho, R
Abstract: Background: Anti-TNF agents are used to treat a variety of autoimmune conditions, including psoriasis. Paradoxically, new onset of psoriasis or psoriasiform skin lesions (PPSL) can occur in patients treated with these agents. We report a case series of patients featuring PPSL induced by infliximab (IFX) with pharmacokinetic and fecal calprotectin (Fc) correlation. Methods: One hundred and thirty-five consecutive patients with Inflammatory Bowel Disease under proactive therapeutic drug monitoring (TDM) with IFX were evaluated for PPSL. Results: Fifteen patients (11.1%) developed PPSL, 12 females (80%), with median age at diagnosis of 52.0 years (38-63). At the onset of PPSL, 6 patients were on 10 mg/kg every 6 weeks, 5 patients on 5 mg/kg every 8 weeks, 2 patients on 10 mg/kg every 4 weeks, 1 patient on 10 mg/kg every 8 weeks, and 1 patent on 5 mg/kg every 6 weeks. In patients with PPSL, IFX trough levels (IFXTL) significantly increased before and after the advent of PPSL: 6.18 µg/mL (3.28-9.91) vs 9.20 µg/mL (5.89-13.91), P= 0.001. At the time of PPSL, all but 2 patients were in Fc remission (< 250 µg/g), median 41 µg/g (30-103). Seven patients improved with topic therapy and 8 patients (53.3%) discontinued IFX (3 switched to ustekinumab) all of which improved. Compared with the overall cohort, IFXTL were higher in patients with PPSL: 7.27 µg/mL (4.02-10.86) vs 6.26 µg/mL (3.37-9.14), P= 0.023. In multivariate regression analysis, female gender [OR 4.84 95%CI (1.23-19.00), P= 0.024], and any IFXTL≥ 10 µg/mL [OR 5.66 95%CI (1.40-22.87), P= 0.015] were independent predictors of developing PPSL. Conclusion: Most patients with PPSL presented high IFXTL and low Fc. We hypothesize that high concentrations of IFX in the setting of deep remission may signal aberrant pro-inflammatory pathways potentially responsible for PPSL.